Letters of Bishop Gabriel to Grigol Dadiani - Abuladze, Nana (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
Bishop Gabrieli played a significant role in the development and reinforcement of the spiritual life of Georgian society in the 19th century. Numerous monographs and scientific works have been prepared to describe the life and achievements of Bishop Gabrieli. The document below aims to present archival materials preserved in the fund of the Dadiani Palaces History and Architectural Museum, which demonstrate the historical relationship between the Bishop of Imereti and Grigol Dadiani. Bishop Gabrieli began his public life during a period when the strong spirit of Georgian society was waning, amidst the historical developments of the first half of the 19th century. Specifically, this was when the Russian Empire abolished Georgia’s statehood and aimed to assimilate the Georgian nation. Gabrieli grew up in a clergyman’s family, and his inner world was filled with love for God and his homeland, leading him to fight against injustice. It is worth mentioning that Bishop Gabrieli had a warm relationship with Grigol Dadiani, the brother of the ruler of Samegrelo region, David Dadiani. The letters preserved in the Dadiani Museum’s collection are significant as they illustrate Grigol Dadiani’s education and literacy. It’s also important to note that Bishop Gabrieli respected Grigol’s views; Grigol played an active role in 19th-century public life as a poet using pen names ‘Kolkhideli’ and ‘Gegechkori,’ as well as a translator who contributed to Georgian culture. The Bishop actively defended the Georgian language, believing that it safeguarded the homeland’s statehood and religion. For him, the Georgian language was a weapon in his struggle, crucial for every Georgian person. Thinking in one’s native language was a cornerstone of the homeland and fertile soil nourishing the nation. In this context, the correspondence between Bishop Gabrieli and the nobleman of Samegrelo, Grigol Dadiani, confirms their relationship during that specific period. These letters are intriguing and important as they reflect respect for literacy and education, modesty, love, a positive relationship, and mutual respect, all of which are highly valued.